2020
DOI: 10.20944/preprints202009.0241.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prebiotic Xylo-oligosaccharides Targeting Faecalibacterium prausnitzii Prevent High Fat Diet-induced Hepatic Steatosis in Rats

Abstract: Understanding the importance of gut microbiota (GM) in non-alcoholic fatty liver disease (NAFLD) has raised the hope for therapeutic microbes. We have shown that high hepatic fat associated with low abundance of Faecalibacterium prausnitzii in humans and further, administration of F. prausnitzii prevented NAFLD in mice. Here, we aimed to target F. prausnitzii by prebiotic xylo-oligosaccharides (XOS) to treat NAFLD. First, the effect of XOS on F. prausnitzii growth was assessed in vitro. Then, XOS was supplemen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Short-chain fatty acids are a primary type of bacterial metabolite produced by bacterial fermentation of otherwise indigestible fibers in the colon (46). Many previous studies have illustrated the role of aberrant levels of SCFAs in NAFLD progression (39,40,(47)(48)(49)(50). SCFAs can disrupt the functioning of the intestinal barrier impairing the translocation of LPS and increasing the level of liver endotoxemia to promote the pathogenesis of NAFLD (50).…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%
See 3 more Smart Citations
“…Short-chain fatty acids are a primary type of bacterial metabolite produced by bacterial fermentation of otherwise indigestible fibers in the colon (46). Many previous studies have illustrated the role of aberrant levels of SCFAs in NAFLD progression (39,40,(47)(48)(49)(50). SCFAs can disrupt the functioning of the intestinal barrier impairing the translocation of LPS and increasing the level of liver endotoxemia to promote the pathogenesis of NAFLD (50).…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%
“…Indeed, previous studies have indicated that gut microbiota directly regulates T-cell immunity through SCFAs (52,53). Moreover, supplementation of a high fiber diet increases the levels of SCFAs, especially butyrate, to promote hepatocyte proliferation (49,54). Butyrate, nicotinate, and 2-oxoglutarate positively regulate hepatic oxidative phosphorylation and negatively regulate TG content through oxidative metabolism.…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Energy expenditure and RER were assessed with indirect calorimetry during a 24 h metabolic cage stay as described previously (Lensu et al, 2020). Briefly, the commercial metabolic cages were equipped with Promethion ® GA3 gas analyzers (Sable Systems, Las Vegas, NV, United States) and FR8 flow generators (Sable Systems) (Lensu et al, 2020). The flow rate was set at 3,000 mL/min and the raw data were processed using ExpeData ® software (Sable Systems).…”
Section: Metabolism and Spontaneous Activitymentioning
confidence: 99%